Assessment of norfloxacin degradation induced by plasma-produced ozone using surface-enhanced Raman spectroscopy. (January 2020) - Huang, Qing; Fang, Cao; Muhammad, Muhammad; Yao, Guohua
Abstract: In this work, we employed surface-enhanced Raman spectroscopy (SERS) combined with density functional theory (DFT) calculation to investigate the pathways/mechanisms of the norfloxacin degradation by oxygen plasma produced ozone. The main degradation products were analyzed by the spectroscopic method, which revealed the breakage of the C–F bond and fracture of piperazinyl and quinolone moieties. In particular, we showed that the main degradation pathway was defluorination of norfloxacin, and this process could be quantitatively assessed by our proposed SERS approach. Graphical abstract: Image 1 Highlights: A special DBD plasma instrument was employed to produce ozone to treat norfloxacin. A novel approach of SERS was applied to analyze the degradation products. The degradation pathways/mechanisms were elucidated using SERS and HPLC-MS. Defluorination of norfloxacin by ozone was proved the main degradation pathway.